2010
DOI: 10.1039/b918439b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of 3-hydroxy-4-pyridinones and their glycosylated derivatives as potential agents for Alzheimer's disease

Abstract: Glycosides of 3-hydroxy-4-pyridinones were synthesized and characterized by mass spectrometry, elemental analysis, (1)H and (13)C NMR spectroscopy, and in one case by X-ray crystallography. The Cu(2+) complex of a novel 3-hydroxy-4-pyridinone was synthesized and characterized by IR and X-ray crystallography, showing the ability of these compounds to chelate potentially toxic metal ions. An MTT cytotoxicity assay of a selected glycosylated compound showed a relatively low toxicity of IC(50) = 570 +/- 90 microM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 60 publications
2
40
1
Order By: Relevance
“…Recently several groups have conceived such new molecules (see Refs. [9][10][11][12][13][14][15][16] and for recent reviews, Refs. [17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently several groups have conceived such new molecules (see Refs. [9][10][11][12][13][14][15][16] and for recent reviews, Refs. [17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
“…5, 12, 14, 17 Given this success we set-out to enhance the antioxidant activity of 1 , without affecting the metal ion chelation capability. 18, 19 The conversion from a pyridine to a pyridol, ( 2 ) was pursued as pyridols are known to react with hydroxyl radicals via addition at the C3 or C5 position of the pyridol ring with the products being reminiscent of tannins, well known for their antioxidant power. 3, 18, 20, 21 Methods used to 2 are detailed in Schemes S1-S3.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] The molecules in this form require the cleavage of the carbohydrate moiety to exert their activity once inside the brain. As a proof, it has been demonstrated that Agrobacterium faecalis glucosidase converts these glucoconjugates in their chelating versions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…β-glucosidases and glucose transporters) and the high levels of Cu 2+ . The rationale behind the development of HQ glucoconjugates(19)(20)(21)(22)(23) resides on glucose avidity of cancer cells (PMT approach) whereas galactoconjugates(24)(25)(26)(27)(28)(29)(30) could exploit ADEPT strategy. Specific β-glucosidases or β-galactosidases can activate HQ glycoconjugates releasing the active aglycone in target cells.…”
mentioning
confidence: 99%